Air-sea interactions during rapid intensification of typhoon Fengshen (2008). (October 2018) - Wang, Xidong; Wang, Xin; Chu, Peter C.
Abstract: Typhoon (TY) Fengshen (2008) rapidly intensified from 35 to 70 kt (about 18–36 m/s) in 24 h between 0000 UTC 19 June and 0000 UTC 20 June 2008 east of the Philippines. Based on multi-platform observations, the oceanic and atmospheric processes responsible for its rapid intensification (RI) is investigated in this study. We find that the anomalously high tropical cyclone heat potential (110–200 kJ/cm 2 ) (TCHP) exerts a great influence on RI of Fengshen compared with other atmospheric environmental factors. In 24 h of RI, TY Fengshen moves over the abnormally warm ocean where the maximum isotherm depth of 26 °C is 200 m which is 80 m deeper than that under the climatological condition. The thick and warm mixed layer restrains the sea surface cooling by limiting entrainment of the cold thermocline water, and thus enhances the ocean to atmosphere heat transfer. In areas of abnormally high TCHP, the occurrence of convective bursts (CBs) results in extra latent heat release (LHR). During the RI phase, abundant LHR causes the warm anomaly of the middle and upper troposphere around the eye, and thereby results in RI of Fengshen. In addition, we also find that the role of high TCHP in CBs and the following RI may be different between asymmetric and axisymmetric processes.